The Search of CH3CN in Interstellar Medium - Chaulagain, UP; Aryal, B; Aryal, MM (Scientific World, 2010)
We present the binding energy, rotational constant, rotational frequency and rotational temperature of CH3CN in different basis sets using Gaussian03. A systematic search of the emission region at 115 GHz is carried out using SkyView Virtual Observatory. A region is selected and studied in the context of rotational temperature of CH3CN using ALADIN2.5 software. From the ab-initio (First principle) calculation of CH3CN in the Hartree Fock level of approximation it is found that there is a strong binding between H, C and N in CH3CN, minimum value of the binding energy being 12.79 eV in the basis set 6-311G which agrees within around 8% to the maximum value of 13.74 eV obtained in the basis set 6-31G*. The estimated value of rotational frequency in the Hartree Fock level of approximation is found to be 322.62 GHz in the basis set 6-31G* which agrees with the values of rotational frequency obtained in other basis sets within around 4%. Similarly, value of rotational temperature in the same basis set 6-31G* is found to be 7.74 K which agrees within around 4% to the corresponding values obtained in other basis sets. The investigation region is a huge (7° × 4°) structure having east to west elongated emission pattern in the CO - survey (115 GHz). We classified this region into three parts (Upper Wing, Lower Wing and Third Region) and study the variation of relative flux density in each pixel. We found that the minimum dust color temperature 8.15 K, 8.04 K and 7.99 K respectively at Upper Wing, Lower Wing and Third Region which are almost 4% differs from rotational temperature CH3CN. This implies that there is strong evidence of possibility of finding CH3CN in the investigated region. But the conformation can only be done by spectral analysis. It is found that the flux density increase from 12 μm to 25 μm and then decreases sharply on moving from 25 μm to 60 μm in the maxima of Upper Wing and Lower wing. The flux density increases but not at significant level when moving from 60 μm to 100 μm. We estimated the dust mass of the three different regions. We found that the mass of Upper Wing, Lower Wing and Third Region are 4273.50 MÈ, 4778.79 Mθ and 2026.75 Mθ respectively. The total mass of the investigated region has to obtain 11079.04 Mθ. The mass of the gas found in the investigated structure is almost 200 times the dust mass. Thus the mass of the investigated structure is found to be 2.22×106 Mθ. Key Words: Interstellar Medium; Flux density; Dust color temperature; Solar mass; Cyanogens. DOI: 10.3126/sw.v7i7.3816 Scientific World Vol.7(7) 2009 pp.10-14